Forest Development Model In Developing Countries In The Era Of Society 5.0 - Adi, Adi Gunawan; Ach. Rifai; Citra Siwi Hanayanti (JOM, 2025)
This research aims to propose sustainable forest management solutions within the framework of Society 5.0. The rapid expansion of industrialization has led to severe environmental challenges, including deforestation and ecological degradation on a global scale. Therefore, this study explores strategies that nations and global communities can adopt to align forest management with societal welfare while ensuring environmental sustainability. This study employs a library research approach, utilizing secondary data and qualitative analysis. The findings reveal several sustainable forest management methods applicable to developing countries to support sustainable development. These methods include leveraging forests for carbon reduction and achieving net-zero carbon emissions, utilizing forest resources for health purposes—either directly or through herbal medicine—and promoting forest-based ecotourism. Additionally, forest management can be integrated with environmental service-based approaches to enhance ecological conservation. Theoretically, this research contributes to the discourse on environmental governance and sustainable development by providing a framework for balancing economic growth with ecological preservation. The findings offer insights for policymakers, environmental scientists, and stakeholders in developing strategies for responsible and innovative forest management in the era of Society 5.0.